Risk analysis in mountain bike, using questionnaire and event tree analysis (ETA) - Dominguez, R.; Correa, F. (Advances in Social and Occupational Ergonomics, 2018)
In this paper, we show the results related with the identification. the actions and conditions which have a negative repercussion on the practice of Downhill, by the application of questionnaire and Event Tree Analysis (ETA). The study includes 265 Amateur and Professional category athletes and observations in races and training zones like Brothers, "Valparaíso Cerro abajo", "Valle el Retiro", among others. Results: The elite category is more susceptible to having a greater number of serious injuries (45.8%) due to the speeds reached within the downhill slopes. The region most affected is the superior limbs (27,5%) due to the natural act of placing hands a number of 1 to 2 serious injuries. This is increased if they perform unsafe actions such as incorrect pedal selection, improper selection of footwear, of which conditions such as poor grip or material fatigue also influence. Conclusion. Focusing on the maintenance and correct conditions of the bicycle, the least performing this practice are Amateur, with 39,8% of the total population that does the sport without maintenance are exposed 55,5% to a number of 3 to 4 mild injuries. ETA give recommendation for each danger situation identified.